IMPLEMENTASI PERATURAN DAERAH KOTA SEMARANG NOMOR 1 TAHUN 2014 TENTANG PENATAAN TOKO MODERN (Kajian Pendirian Minimarket di Kecamatan Banyumanik Kota Semarang) - Devi Nur Puspitasari; Ari Subowo (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2016)
The development of minimarkets in Semarang by the end of year have increased. In 2014, Badan Pelayanan Perijinan Terpadu (BPPT) Semarang has delivered 119 Ijin Usaha Toko Modern (IUTM) which the most trade license of minimarket is in Banyumanik. Increasingly the minimarket investment on Peraturan Daerah Kota Semarang Nomor 1 Tahun 2014 tentang Penataan Toko Modern and Peraturan Walikota Semarang Nomor 5 Tahun 2013 tentang Penataan Toko Modern Minimarket Kota Semarang. The purpose of policy is to keep the growth balance between minimarket and the figure of micro trade. While commit, there still have any obstacles such as the regulation of minimarket in Semarang which has to built >500m from tradisional market exactly around of Rasamala market has built some minimarkets less than 200m from traditional market. Besides, the government limits the establishment quota based on the trade license which has been delivered. Minimarket quota restrictions only with IUTM and in fact there are many minimarkets operating without a business license pocketed. Therefore, the government should also coordinate with the sub-district to conduct surveillance to monitoring of the development minimarket